Oblique Semi-Guided Waves: 2-D Integrated Photonics with Negative Effective Permittivity - Hammer, Manfred; Ebers, Lena; Hildebrandt, Andre; Alhaddad, Samer; Förstner, Jens (2018 IEEE 17th International Conference on Mathematical Methods in Electromagnetic Theory (MMET))
Semi-guided waves confined in dielectric slab waveguides are being considered for oblique angles of propagation. If the waves encounter a linear discontinuity of (mostly) arbitrary shape and extension, a variant of Snell's law applies, separately for each pair of incoming and outgoing modes. Depending on the effective indices involved, and on the angle of incidence, power transfer to specific outgoing waves can be allowed or forbidden. In particular, critical angles of incidence can be identified, beyond which any power transfer to non-guided waves is forbidden, i.e. all radiative losses are suppressed. In that case the input power is carried away from the discontinuity exclusively by reflected semi-guided waves in the input slab, or by semi-guided waves that are transmitted into other outgoing slab waveguides. Vectorial equations on a 2-D cross sectional domain apply. These are formally identical to the equations that govern the eigenmodes of 3-D channel waveguides. Here, however, these need to be solved not as an eigenvalue problem, but as an inhomogeneous problem with a right-hand-side that is given by the incoming semi-guided wave, and subject to transparent boundary conditions. The equations resemble a standard 2-D Helmholtz problem, with an effective permittivity in place of the actual relative permittivity. Depending on the properties of the incoming wave, including the angle of incidence, this effective permittivity can become locally negative, causing the suppression of propagating outgoing waves. A series of high-contrast example configurations are discussed, where these effects lead to - in some respects - quite surprising transmission characteristics.
Keywords: tet_topic_waveguides

Decay and revival of electron spin polarization in an ensemble of (In,Ga)As quantum dots - Evers, E.; Belykh, V. V.; Kopteva, N. E.; Yugova, I. A.; Greilich, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Interlayer charge transfer in n-modulation doped Al1−x Ga x As–GaAs single heterostructures - Schuster, J; Kim, T Y; Batke, E; Reuter, Dirk; Wieck, A D (Semiconductor Science and Technology)

Basic Requirements of Spin-Flip Raman Scattering on Excitonic Resonances and Its Modulation through Additional High-Energy Illumination in Semiconductor Heterostructures - Debus, J.; Kudlacik, D.; Sapega, V. F.; Shamirzaev, T. S.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Waag, A.; Bayer, M. (Physics of the Solid State)

Formation of self-assembled GaAs quantum dots via droplet epitaxy on misoriented GaAs(111)B substrates - Trapp, Alexander; Reuter, Dirk (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics: Materials, Processing, Measurement, and Phenomena)

Site-controlled droplet epitaxy of GaAs quantum dots by deposition through shadow masks - Zolatanosha, Viktoryia; Reuter, Dirk (Journal of Vacuum Science & Technology B, Nanotechnology and Microelectronics: Materials, Processing, Measurement, and Phenomena)

Spin inertia of resident and photoexcited carriers in singly charged quantum dots - Zhukov, E. A.; Kirstein, E.; Smirnov, D. S.; Yakovlev, D. R.; Glazov, M. M.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Greilich, A. (Physical Review B)

Optical Properties of Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Nonlinear Quasi-Phase Matching with metasurfaces - Heron, S.; Reineke, B.; Vezian, S.; Zentgraf, Thomas; Damilano, B.; Genevet, P. (2018 12th International Congress on Artificial Materials for Novel Wave Phenomena (Metamaterials))

Near-field plasmonic beam engineering by complex amplitude modulation based on metasurface (Conference Presentation) - Sun, Lin; Zhang, Xiaomeng; Zhao, Ruizhe; Li, Xiaowei; Wang, Jia; Bai, Benfeng; Wang, Yongtian; Zentgraf, Thomas; Huang, Lingling; Song, Xu (Nanophotonics VII)

Unveiling and Imaging Degenerate States in Plasmonic Nanoparticles with Nanometer Resolution - Myroshnychenko, Viktor; Nishio, Natsuki; García de Abajo, F. Javier; Förstner, Jens; Yamamoto, Naoki (ACS Nano)
Metal nanoparticles host localized plasmon excitations that allow the manipulation of optical fields at the nanoscale. Despite the availability of several techniques for imaging plasmons, direct access into the symmetries of these excitations remains elusive, thus hindering progress in the development of applications. Here, we present a combination of angle-, polarization-, and space-resolved cathodoluminescence spectroscopy methods to selectively access the symmetry and degeneracy of plasmonic states in lithographically fabricated gold nanoprisms. We experimentally reveal and spatially map degenerate states of multipole plasmon modes with nanometer spatial resolution and further provide recipes for resolving optically dark and out-of-plane modes. Full-wave simulations in conjunction with a simple tight-binding model explain the complex plasmon structure in these particles and reveal intriguing mode-symmetry phenomena. Our approach introduces systematics for a comprehensive symmetry characterization of plasmonic states in high-symmetry nanostructures.
Keywords: tet_topic_plasmonics

Third Harmonic Generation Enhanced by Multipolar Interference in Complementary Silicon Metasurfaces - Chen, Shumei; Rahmani, Mohsen; Li, King Fai; Miroshnichenko, Andrey; Zentgraf, Thomas; Li, Guixin; Neshev, Dragomir; Zhang, Shuang (ACS Photonics)

Spin and Geometric Phase Control Four-Wave Mixing from Metasurfaces - Li, Guixin; Sartorello, Giovanni; Chen, Shumei; Nicholls, Luke H.; Li, King Fai; Zentgraf, Thomas; Zhang, Shuang; Zayats, Anatoly V. (Laser & Photonics Reviews)

Editorial for the theories and applications of metasurfaces - Guo, Zhongyi; Chen, Xianzhong; Zentgraf, Thomas (Journal of Physics D: Applied Physics)

Controlling the phase of optical nonlinearity with plasmonic metasurfaces - Chen, Shumei; Li, Guixin; Cheah, Kok Wai; Zentgraf, Thomas; Zhang, Shuang (Nanophotonics)

Nanoscale Polarization Manipulation and Encryption Based on Dielectric Metasurfaces - Zhao, Ruizhe; Huang, Lingling; Tang, Chengchun; Li, Junjie; Li, Xiaowei; Wang, Yongtian; Zentgraf, Thomas (Advanced Optical Materials)

Tailored UV Emission by Nonlinear IR Excitation from ZnO Photonic Crystal Nanocavities - Hoffmann, Sandro P.; Albert, Maximilian; Weber, Nils; Sievers, Denis; Förstner, Jens; Zentgraf, Thomas; Meier, Cedrik (ACS Photonics)
Keywords: tet_topic_phc

Efficient frequency conversion by combined photonic–plasmonic mode coupling - Weber, N.; Hoffmann, S. P.; Albert, M.; Zentgraf, Thomas; Meier, Cedrik (Journal of Applied Physics)

Erratum: Optical properties of titanium-doped lithium niobate from time-dependent density-functional theory [Phys. Rev. Materials 1, 034401 (2017)] - Friedrich, Michael; Schmidt, Wolf Gero; Schindlmayr, Arno; Sanna, Simone (Physical Review Materials)

Vortex Multistability and Bessel Vortices in Polariton Condensates. - Ma, Xuekai; Schumacher, Stefan (Physical Review Letters)

64 GBd Monolithically Integrated Coherent QPSK Single Polarization Receiver in 0.25 µm SiGe-Photonic Technology - Kress, Christian; Gudyriev, Sergiy; Zwickel, Heiner; Kemal, Juned N.; Lischke, Stefan; Zimmermann, Lars; Koos, Christian; Scheytt, Christoph (Optical Fiber Communication Conference 2018, San Diego)
A monolithically integrated coherent receiver in silicon photonic technology is presented along with measurement results for constellation diagrams up to 64GBd and bandwidth of 34 GHz. To our knowledge this is the fastest single-chip coherent receiver.

Electronic Photonic Integrated Circuits for Coherent and Non-Coherent Receivers - Gudyriev, Sergiy; Kress, Christian; Scheytt, Christoph (10th Sino-German Joint Symposium on Opto- and Microelectronic Devices and Circuits (SODC 2018))

Ultra‐broadband Signal Processing by means of Electronic‐Photonic Integration - Scheytt, Christoph (10th Sino-German Joint Symposium on Opto- and Microelectronic Devices and Circuits (SODC 2018))

Electronic‐Photonic Integrated Systems for Ultrafast Signal Processing - Gudyriev, Sergiy; Kress, Christian; Scheytt, Christoph (DFG Priority Programme SPP2111)

Switchable Plasmonic Metasurface Utilizing the Electro-Optic Kerr Effect of a Blue Phase Liquid Crystal - Atorf, Bernhard; Friesen, Simon; Rennerich, Roman; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)

Switchable Plasmonic Holograms Utilizing the Electro-Optic Effect of a Liquid-Crystal Circular Polarizer - Atorf, Bernhard; Rasouli, Hoda; Mühlenbernd, Holger; Reineke, Bernhard J.; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Switchable Plasmonic Metasurface Utilizing the Electro-Optic Kerr Effect of a Blue Phase Liquid Crystal - Atorf, Bernhard; Friesen, Simon; Rennerich, Roman; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)

Liquid crystalline dithienothiophene derivatives for organic electronics - Vollbrecht, Joachim; Oechsle, Peter; Stepen, Arne; Hoffmann, Florian; Paradies, Jan; Meyers, Thorsten; Hilleringmann, Ulrich; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried (Organic Electronics)

Blends of Two Perylene Derivatives: Mesogenic Properties and Application As Emitter Materials in OLEDs - Vollbrecht, Joachim; Stepen, Arne; Nolkemper, Karlo; Keuker-Baumann, Susanne; Kitzerow, Heinz-Siegfried (Polymer Science, Series C)
Keywords: Materials Chemistry; Polymers and Plastics; General Chemistry

Ultrafast electric phase control of a single exciton qubit - Widhalm, Alex; Mukherjee, Amlan; Krehs, Sebastian; Sharma, Nandlal; Kölling, Peter; Thiede, Andreas; Reuter, Dirk; Förstner, Jens; Zrenner, Artur (Applied Physics Letters)
We report on the coherent phase manipulation of quantum dot excitons by electric means. For our experiments, we use a low capacitance single quantum dot photodiode which is electrically controlled by a custom designed SiGe:C BiCMOS chip. The phase manipulation is performed and quantified in a Ramsey experiment, where ultrafast transient detuning of the exciton energy is performed synchronous to double pulse p/2 ps laser excitation. We are able to demonstrate electrically controlled phase manipulations with magnitudes up to 3p within 100 ps which is below the dephasing time of the quantum dot exciton.
Keywords: tet_topic_qd

Theory of optically controlled anisotropic polariton transport in semiconductor double microcavities - Luk, Samuel M. H.; Lewandowski, P.; Kwong, N. H.; Baudin, E.; Lafont, O.; Tignon, J.; Leung, P. T.; Chan, Ch. K. P.; Babilon, M.; Schumacher, Stefan; Binder, R. (Journal of the Optical Society of America B)

Bright squeezed vacuum in a nonlinear interferometer: Frequency and temporal Schmidt-mode description - Sharapova, Polina R.; Tikhonova, O. V.; Lemieux, S.; Boyd, R. W.; Chekhova, M. V. (Physical Review A)

Microscopic theory of cavity-enhanced single-photon emission from optical two-photon Raman processes - Breddermann, Dominik; Praschan, Tom; Heinze, Dirk Florian; Binder, Rolf; Schumacher, Stefan (Physical Review B)

Manipulation of Two-Photon Interference by Entanglement - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Silberhorn, Christine; Meier, Torsten (Conference on Lasers and Electro-Optics)

Exotic complexes in one-dimensional Bose-Einstein condensates with spin-orbit coupling - Belobo, D. Belobo; Meier, Torsten (Scientific Reports)

Monolithically Integrated Hong-Ou-Mandel Experiment in LiNbO3 - Luo, Kai Hong; Brauner, Sebastian; Eigner, Christof; Sharapova, Polina; Ricken, Raimund; Meier, Torsten; Herrmann, Harald; Silberhorn, Christine (Conference on Lasers and Electro-Optics)

Foundations of Coherent Transients in Semiconductors - Meier, Torsten; Koch, S.W. (Encyclopedia of Modern Optics (Second Edition))
Short laser pulses are able to generate material excitations with a well-defined phase which is imposed by the optical excitation source. The generated coherent superposition state be described as an optical polarization which exists only in non-equilibrium situations. The coherence, i.e., the phase relations between the optical transitions that originate from the excitation, leads to several interesting effects in time-resolved linear and nonlinear optical spectroscopy. In this article, the basic principles that underlie these coherent transients are introduced and several examples are presented.

Signatures of transient Wannier-Stark localization in bulk gallium arsenide - Schmidt, C.; Bühler, J.; Heinrich, A.-C.; Allerbeck, J.; Podzimski, R.; Berghoff, D.; Meier, Torsten; Schmidt, Wolf Gero; Reichl, C.; Wegscheider, W.; Brida, D.; Leitenstorfer, A. (Nature Communications)

Signatures of transient Wannier-Stark localization in bulk gallium arsenide - Schmidt, Claudia; Bühler, J.; Heinrich, A.-C.; Allerbeck, J.; Podzimski, R.; Berghoff, Daniel; Meier, Torsten; Schmidt, Wolf Gero; Reichl, C.; Wegscheider, W.; Brida, D.; Leitenstorfer, A. (Nature Communications)

Observation and Uses of Position-Space Bloch Oscillations in an Ultracold Gas - Geiger, Zachary A.; Fujiwara, Kurt M.; Singh, Kevin; Senaratne, Ruwan; Rajagopal, Shankari V.; Lipatov, Mikhail; Shimasaki, Toshihiko; Driben, Rodislav; Konotop, Vladimir V.; Meier, Torsten; Weld, David M. (Physical Review Letters)

Observation and Uses of Position-Space Bloch Oscillations in an Ultracold Gas - Geiger, Zachary A.; Fujiwara, Kurt M.; Singh, Kevin; Senaratne, Ruwan; Rajagopal, Shankari V.; Lipatov, Mikhail; Shimasaki, Toshihiko; Driben, Rodislav; Konotop, Vladimir V.; Meier, Torsten; Weld, David M. (Physical Review Letters)

Nonlinearity-induced localization in a periodically driven semidiscrete system - Driben, R.; Konotop, V. V.; Malomed, B. A.; Meier, Torsten; Yulin, A. V. (Physical Review E)

Coherent optical spectroscopy of charged exciton complexes in semiconductor nanostructures - Akimov, Ilya; Poltavtsev, Sergey V.; Salewski, Matthias; Yugova, Irina A.; Karczewski, Grzegorz; Wojtowicz, Tomasz; Maciej, Wiater; Reichelt, Matthias; Meier, Torsten; Yakovlev, Dmitri; Bayer, Manfred (Ultrafast Phenomena and Nanophotonics XXII)

Coherent optical spectroscopy of charged exciton complexes in semiconductor nanostructures - Akimov, Ilya; Poltavtsev, Sergey V.; Salewski, Matthias; Yugova, Irina A.; Karczewski, Grzegorz; Wojtowicz, Tomasz; Maciej , Wiater; Reichelt, Matthias; Meier, Torsten; Yakovlev, Dmitri; Bayer, Manfred (Ultrafast Phenomena and Nanophotonics XXII)

Nonlinearity-induced localization in a periodically driven semidiscrete system - Driben, R.; Konotop, V. V.; Malomed, B. A.; Meier, Torsten; Yulin, A. V. (Physical Review E)

Coherent ePIC Receiver for 64 GBaud QPSK in 0.25μm Photonic BiCMOS Technology - Gudyriev, Sergiy; Kress, Christian; Zwickel, Heiner; Kemal, Juned N.; Lischke, Stefan; Zimmermann, Lars; Koos, Christian; Scheytt, Christoph (IEEE/OSA Journal of Lightwave Technology)
In this paper, we present a monolithically integrated coherent receiver with on-chip grating couplers, 90° hybrid, photodiodes and transimpedance amplifiers. A transimpedance gain of 7.7 kΩ was achieved by the amplifiers. An opto-electrical 3 dB bandwidth of 34 GHz for in-phase and quadrature channel was measured. A real-time data transmission of 64 GBd-QPSK (128 Gb/s) for a single polarization was performed.

Imaging of 180∘ ferroelectric domain walls in uniaxial ferroelectrics by confocal Raman spectroscopy: Unraveling the contrast mechanism - Rüsing, Michael; Neufeld, Sergej; Brockmeier, Julian; Eigner, Christof; Mackwitz, P.; Spychala, K.; Silberhorn, Christine; Schmidt, Wolf Gero; Berth, Gerhard; Zrenner, Artur; Sanna, S. (Physical Review Materials)
In recent years, Raman spectroscopy has been used to visualize and analyze ferroelectric domain structures. The technique makes use of the fact that the intensity or frequency of certain phonons is strongly influenced by the presence of domain walls. Although the method is used frequently, the underlying mechanism responsible for the changes in the spectra is not fully understood. This inhibits deeper analysis of domain structures based on this method. Two different models have been proposed. However, neither model completely explains all observations. In this work, we have systematically investigated domain walls in different scattering geometries with Raman spectroscopy in the common ferroelectric materials used in integrated optics, i.e., KTiOPO4, LiNbO3, and LiTaO3. Based on the two models, we can demonstrate that the observed contrast for domain walls is in fact based on two different effects. We can identify on the one hand microscopic changes at the domain wall, e.g., strain and electric fields, and on the other hand a macroscopic change of selection rules at the domain wall. While the macroscopic relaxation of selection rules can be explained by the directional dispersion of the phonons in agreement with previous propositions, the microscopic changes can be explained qualitatively in terms of a simplified atomistic model.

Stacked Self-Assembled Cubic GaN Quantum Dots Grown by Molecular Beam Epitaxy - Blumenthal, Sarah; Rieger, Torsten; Meertens, Doris; Pawlis, Alexander; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
We have investigated the stacking of self-assembled cubic GaN quantum dots (QDs) grown in Stranski–Krastanov (SK) growth mode. The number of stacked layers is varied to compare their optical properties. The growth is in situ controlled by reflection high energy electron diffraction to prove the SK QD growth. Atomic force and transmission electron microscopy show the existence of wetting layer and QDs with a diameter of about 10 nm and a height of about 2 nm. The QDs have a truncated pyramidal form and are vertically aligned in growth direction. Photoluminescence measurements show an increase of the intensity with increasing number of stacked QD layers. Furthermore, a systematic blue-shift of 120 meV is observed with increasing number of stacked QD layers. This blueshift derives from a decrease in the QD height, because the QD height has also been the main confining dimension in our QDs.
Keywords: cubic crystals; GaN; molecular beam epitaxy; quantum dots

High-Q whispering gallery microdisk resonators based on silicon oxynitride - Hett, T.; Krämmer, S.; Hilleringmann, U.; Kalt, H.; Zrenner, Artur (JOURNAL OF LUMINESCENCE)
In this article we demonstrate a fully CMOS compatible fabrication process for the realization of microdisk resonators based on silicon oxynitride. The layer fabrication using plasma enhanced chemical vapor deposition is optimized in terms of surface roughness and internal material absorption. Resulting surface roughness due to the etching process is reduced by using optimized etching parameters. Whispering gallery modes of the fabricated microdisk resonators have been investigated by tapered fiber coupling and show quality factors as high as 10 6.

Polarization-entangled twin photons from two-photon quantum-dot emission - Heinze, Dirk; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum dots are promising sources for polarization-entangled photons. As an alternative to the usual cascaded biexciton-exciton emission, direct two-photon emission from the biexciton can be used. With a high-quality optical resonator tuned to half the biexciton energy, a large proportion of the photons can be steered into the two-photon emission channel. In this case the degree of polarization entanglement is inherently insensitive to the exciton fine-structure splitting. In the present work we analyze the biexciton emission with particular emphasis on the influence of coupling of the quantum-dot cavity system to its environment. Especially for a high-quality cavity, the coupling to the surrounding semiconductormaterial can open up additional phonon-assisted decay channels. Our analysis demonstrates that with the cavity tuned to half the biexciton energy, the potentially detrimental influence of the phonons on the polarization entanglement is strongly suppressed—high degrees of entanglement can still be achieved. We further discuss spectral properties and statistics of the emitted twin photons.